2022
DOI: 10.3390/pr10010151
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Post- and Pre-Acid Treatment during Hydrothermal Carbonization of Sewage Sludge on P-Transformation and the Characteristics of Hydrochar

Abstract: Phosphorus (P) recovery from alternative P-rich residues is essential to meet the growing demands of food production globally. Despite sewage sludge being a potential source for P, its direct application on agricultural land is controversial because of the obvious concerns related to heavy metals and organic pollutants. Further, most of the available P recovery and sludge management technologies are cost-intensive as they require mandatory dewatering of sewage sludge. In this regard, hydrothermal carbonization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The results showed that water only had a minor effect on extraction, whereas the addition of sulfuric acid can leach significant amounts of phosphorus into the process water during HTC [44]. Shettigondahalli et al [56] again conducted HTC trials with sewage sludge and the addition of sulfuric acid before and after HTC. The authors observed that, in contrast to acid leaching after HTC, a significantly lower concentration of phosphorus was converted from the solid phase to the liquid phase by the addition of sulfuric acid before HTC [56].…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that water only had a minor effect on extraction, whereas the addition of sulfuric acid can leach significant amounts of phosphorus into the process water during HTC [44]. Shettigondahalli et al [56] again conducted HTC trials with sewage sludge and the addition of sulfuric acid before and after HTC. The authors observed that, in contrast to acid leaching after HTC, a significantly lower concentration of phosphorus was converted from the solid phase to the liquid phase by the addition of sulfuric acid before HTC [56].…”
Section: Overviewmentioning
confidence: 99%
“…Shettigondahalli et al [56] again conducted HTC trials with sewage sludge and the addition of sulfuric acid before and after HTC. The authors observed that, in contrast to acid leaching after HTC, a significantly lower concentration of phosphorus was converted from the solid phase to the liquid phase by the addition of sulfuric acid before HTC [56].…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of studies in Table 1 have also investigated the effect of pH adjustment on P speciation and migration during HT treatments of SS [7,33,48,52,66,72,75,81,91,[103][104][105][106]. Indeed, adsorption, precipitation, and other P-related chemical reactions are considerably affected by pH [107].…”
Section: Acidic and Basic Treatmentsmentioning
confidence: 99%
“…NaOH is generally used to increase the medium pH [48,52,66,72,81,91,103]. Acid solutions used in the selected works include hydrochloric acid [7,52,66,72,91], nitric acid [33,48,104], sulfuric acid [75,103,105], formic acid [103], acetic acid [81,103], and citric acid [106].…”
Section: Acidic and Basic Treatmentsmentioning
confidence: 99%